Faculty Business And Management Fundamentals of Entrepreneurship Topic: Business Plan (BP) / Muhammad Fauzi Mahamad Saad - Mahamad Saad, Muhammad Fauzi (2019)
Encouraging consumers to aware about the content of the soap used as for example between coconut oil and pig oil. Making it easier for working mothers to handle their household matters. Prioritize the cleanliness of the clothes, home and personal in efficient and effective way. Foster the spirit of product support by Muslims in market place. Provide products with affordable price and has satisfactory quality and results.